Earthworm species diversity across an elevational gradient in Mt. Sawtooth and its neighboring highlands in the Zambales Mountain Range, the Philippines - Angeles, Ericka Jane A. (Philippine Journal of Science, 2024)
Earthworm species diversity was determined across an elevational gradient in Mt. Sawtooth and nearby highlands in the Zambales Mountain Range, part of the Tarlac province, Philippines. This study documented 34 earthworm morphospecies with one exotic species, Pontoscolex corethrurus, and 33 morphospecies belonging to the family Megascolecidae. Megascolecid earthworms were assigned to the following genera: Pheretima, Pithemera, Pleionogaster, Archipheretima, and Polypheretima. Two main clusters of earthworm assemblages were identified based on Jaccard’s index – a cluster characterized by low species richness and dominance of P. corethrurus, as well as a cluster characterized by diverse megascolecid earthworm genera. Most megascolecid earthworms were found in sites with broad canopy cover, high soil moisture, and high relative humidity with low air temperature, low soil temperature, and low soil pH. Anthropogenic disturbances such as reforestation using non-native tree species may have negatively affected the earthworm diversity in lower elevations, as these activities can modify soil properties and destroy natural habitats, making the conditions ideal for the invasion by P. corethrurus. The diversity of megascolecid earthworms in higher elevations was attributed in part to the geological history of the Zambales Mountain Range.